Prevalence of Trachoma in Upper Sindh - Dureyakta Shaikh, Abdul Qadir Shaikh, Muhammad Hashim Qureshi, Shahid Jamal Siddiqui Muhammad Afzal Pechuho (Pakistan Journal of Ophthalmology, 2010)
Purpose: To determine the prevalence of trachoma in upper Sindh. Material and Methods: We did cross sectional study simultaneously at Ghulam Muhammad Mahar Medical College Sukkur, Chandka medical college Larkana and Civil Hospital Jacobabad from 1st Jan 2007 to 20th April 2009. Patients suffering from clinical features of active trachoma and trachomatous trichiasis were examined. We diagnosed patients on clinical grounds using W.H.O simplified Grading system. Result: Nine Thousand and six patients with trachoma were diagnosed, Eight thousand seven hundred (96.6%) with active trachoma and 306 (3.40%) with trichaisis. Active trachoma was highly prevalent in female children (48.97%) while trachomatous trachiasis was predominantly seen in adult females (6.7%). Conclusion: Active trachoma is still an avoidable vision threatening challenge in upper Sindh. A Collaborated wide ranging integrated community based approach must be implicated to reach elimination of trachoma by the year 2020.